2021
DOI: 10.1186/s12974-021-02248-2
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid alleviates secondary injury in spinal cord injury mice by reducing oxidative stress, apoptosis, and inflammatory response

Abstract: Background Tauroursodeoxycholic acid (TUDCA) is a hydrophilic bile acid derivative, which has been demonstrated to have neuroprotective effects in different neurological disease models. However, the effect and underlying mechanism of TUDCA on spinal cord injury (SCI) have not been fully elucidated. This study aims to investigate the protective effects of TUDCA in the SCI mouse model and the related mechanism involved. Methods The primary cortical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 50 publications
(51 reference statements)
5
52
1
Order By: Relevance
“…After SCI, a high amount of MDA and ROS was produced in the injury site. Over time, GSH-Px and SOD are produced to remove the free radicals and scavenge ROS-induced lipid peroxides to protect the tissue function [ 35 ]. To evaluate the inhibitory effects of SeNPs at different concentrations on the oxidative stress of the SCI rats in vivo , the expressions of MDA, ROS, SOD, and GSH-Px were detected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After SCI, a high amount of MDA and ROS was produced in the injury site. Over time, GSH-Px and SOD are produced to remove the free radicals and scavenge ROS-induced lipid peroxides to protect the tissue function [ 35 ]. To evaluate the inhibitory effects of SeNPs at different concentrations on the oxidative stress of the SCI rats in vivo , the expressions of MDA, ROS, SOD, and GSH-Px were detected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, TUDCA was more efficacious than UDCA in reducing microglial activation. One study reported the comparative efficacy of TUDCA and UDCA in a laser-induced choroidal neovascularization (CNV) model, showing similar effects in terms of CNV suppression [ 13 ]. However, only TUDCA was associated with early inhibition of VEGF in the retina after laser injury, which indicates that other mechanisms might be involved in the suppression of CNV by UDCA.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory and antioxidant effects have been reported for TUDCA in photoreceptor degeneration models [ 8 , 9 , 12 ]. Additionally, TUDCA showed beneficial effects on axonal regeneration and amyloid-beta synaptic toxicity in a spinal cord injury model and in cortical neurons [ 12 , 13 ]. The neuroprotective effect of UDCA also has been demonstrated, although in a limited number of animal models [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It allows clearance of debris, restores tissue homeostasis, and promotes tissue repair by inhibiting inflammation through the production of anti-inflammatory, neurotrophic factors, and chemokine receptors [ 14 16 , 18 ]. Several M2 phenotype markers characterize this M2 state, e.g., the enzyme Arginase 1 (ARG1), a marker of microglia involved in tissue repair and phagocytosis, the receptor CD163, a marker of microglia implicated in the anti-inflammatory process and healing, IL-10, an anti-inflammatory cytokine used by the M2 subtype to antagonize the pro-inflammatory phase and healing, and TNFα-stimulated gene-6 (TSG-6/TNFAIP6), which is a key anti-inflammatory factor produced by MSCs [ 19 22 ]. Reducing the pro-inflammatory M1 phenotype or inducing M2 microglial polarization might represent a potential and promising therapeutic option to treat neuroinflammatory degenerative diseases such as glaucoma [ 9 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%